Upaya Meningkatkan Hasil Belajar Melalui Penggunaan Media Power Point pada Pembelajaran Tematik Siswa Kelas III - Nurhidayah Nurhidayah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study is to improve student learning outcomes in thematic learning. This research is a classroom action research (PTK) which is carried out in three cycles, each cycle consisting of planning, implementing, observing, and reflecting stages. The subjects of this study were students of class III SD Negeri Kedawung 02, Kroya District, Cilacap Regency in the academic year 2020/2021, totaling 22 students. Data collection techniques using tests and observations. This study shows that the use of power point media can improve learning outcomes in thematic learning of class III SD Negeri Kedawung 02 in the 2020/2021 academic year as evidenced by the percentage of completeness of learning outcomes in cycle I of 77.3%, cycle II of 90.1% , and cycle III reaches 100%.